2006
DOI: 10.1161/01.str.0000221331.01830.ce
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Delayed Rebleeding From Intracranial Aneurysms Are Low After Surgical and Endovascular Treatment

Abstract: Background and Purpose-Although results of the randomized International Subarachnoid Aneurysm Trial suggested that coil embolization was superior to surgical clipping 1 year after treatment, a paucity of data on long-term outcomes has been a major concern. Methods-In an ambidirectional cohort study, 9 institutions with expertise in intracranial aneurysm treatment identified all ruptured saccular aneurysms treated 1996 to 1998. After an initial medical record review, all patients meeting entry criteria were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(41 citation statements)
references
References 18 publications
3
34
1
1
Order By: Relevance
“…There are currently at least two options for the acute treatment of a ruptured aneurysm: endovascular coiling or surgical clipping. Treatment of a recently ruptured aneurysm reduces the rate of rebleeding, and the benefit is related to the time to treatment initiation[162]. Current guidelines recommend that surgical clipping or endovascular coiling should be performed to reduce the rate of rebleeding after aneurysmal SAH, and these procedures should be performed early in the disease course.…”
Section: Aneurysm Repairmentioning
confidence: 99%
“…There are currently at least two options for the acute treatment of a ruptured aneurysm: endovascular coiling or surgical clipping. Treatment of a recently ruptured aneurysm reduces the rate of rebleeding, and the benefit is related to the time to treatment initiation[162]. Current guidelines recommend that surgical clipping or endovascular coiling should be performed to reduce the rate of rebleeding after aneurysmal SAH, and these procedures should be performed early in the disease course.…”
Section: Aneurysm Repairmentioning
confidence: 99%
“…Despite the focus on RIAs, important information can be learned from the ISAT 8 and Cerebral Aneurysm Rerupture After Treatment (CARAT) 320 studies. Long-term follow-up data (mean, 9 years) on 2004 treated patients from the initial ISAT report reveal 24 rehemorrhages, 13 of which were from the treated aneurysm (10 treated by coiling and 3 by clipping).…”
mentioning
confidence: 99%
“…Thus, endovascular embolization allows the elimination of the aneurysm with minimal interruption of blood supply to the brain. However, endovascular embolization presents a relatively high risk of aneurysm recurrence compared with the more invasive surgical closure, due to the fact that vascular endothelium may not be fully anastomosed at the aneurysm neck [2426]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that an aneurismal SAH recurrence is 15–22 times more likely than the expected rate of a first SAH [34,35]. A study showed aneurysm recurrence in 8% of patients treated with coil embolization [26]. In a large series, 34% had an aneurysm recurrence in the 12 months following embolization [21].…”
Section: Discussionmentioning
confidence: 99%